Kepuasan Kerja Staf Puskesmas Rawat Jalan dan Puskesmas Rawat Inap di Kabupaten Kotawaringin Barat - Togar Hasudungan Manurung; Martha Irene Kartasurya; Ayun Sriatmi (Malahayati Nursing Journal, 2022)
ABSTRACT Health staff job satisfaction has an impact on performance. The Puskesmas has periodically measured customer satisfaction but staff job satisfaction has never been done. From the preliminary study, it was found that the job satisfaction of puskesmas staff in Kotawaringin Barat Regency was still low. To find out the difference in job satisfaction of inpatient puskesmas staff with outpatient health centers. Cross sectional research design with a quantitative approach. The study population was inpatient and outpatient puskesmas staff in Kotawaringin Barat Regency. Subject recruitment was done through the puskesmas. From 14 outpatient health centers, 3 puskesmas were selected and from 4 inpatient puskesmas 2 were selected. A total of 40 subjects filled out a questionnaire that was distributed electronically. Data analysis was carried out using an independent t test to distinguish job satisfaction. High job satisfaction at outpatient health centers is on the factor of supervision, and policies respectively by 62%, motivation 57%, while low satisfaction in the physical work environment 19%, on factors of safety and work safety, incentives, capitation services each 33%, and work culture 38%. High job satisfaction at inpatient health centers in the form of work culture factors, and capitation services each by 68%, work results 63%, and 58% each on co-workers factors, work security and safety, opportunities to improve skills and skills, while low satisfaction in the physical work environment 16%, incentives 16%, workload 37%, supervision 42%, and policy 42%. There was no significant difference between job satisfaction at outpatient puskesmas and inpatient puskesmas (p=0.317). The job satisfaction of outpatient clinics is on the factors of supervision, the policy of the Head of the Puskesmas, and motivation. At inpatient health centers in the form of work culture, capitation services, work results, colleagues, work security and safety, opportunities to improve skills and expertise. Keywords: Job Satisfaction, Puskesmas, Inpatient, Outpatient, Health Workers  ABSTRAK Kepuasan kerja staf kesehatan berdampak pada kinerja. Puskesmas secara periodik sudah melakukan pengukuran  kepuasan pelanggan tetapi kepuasan kerja staf belum pernah dilakukan. Dari studi pendahuluan didapatkan bahwa kepuasan kerja staf puskesmas di Kabupaten Kotawaringin Barat masih rendah. Tujuan untuk mengetahui perbedaan kepuasan kerja staf puskesmas rawat inap dengan puskesmas rawat jalan. Desain penelitian cross sectional dengan pendekatan kuantitatif. Populasi penelitian staf puskesmas rawat inap dan rawat jalan di Kabupaten Kotawaringin Barat. Rekrutmen subjek dilakukan melalui puskesmas. Dari 14 puskesmas rawat jalan dipilih 3 puskesmas dan dari 4 puskesmas rawat inap dipilih 2 puskesmas. Sebanyak 40 subjek mengisi angket yang disebarkan secara elektronik. Analisa data dilakukan dengan uji independent t test untuk membedakan kepuasan kerja. Kepuasan kerja yang tinggi pada puskesmas rawat jalan adalah pada faktor pengawasan, dan kebijakan masing-masing sebesar 62%, motivasi 57%, sedangkan kepuasan yang rendah pada lingkungan kerja fisik 19%, pada faktor keamanan dan keselamatan kerja, insentif, jasa kapitasi masing-masing 33%, dan budaya kerja 38%. Kepuasan kerja yang tinggi pada puskesmas rawat inap berupa faktor budaya kerja, dan jasa kapitasi masing-masing sebesar 68%, hasil pekerjaan 63%, dan masing-masing 58% pada faktor rekan kerja, keamanan dan keselamatan kerja, kesempatan meningkatkan keahlian dan keterampilan, sedangkan kepuasan yang rendah pada lingkungan kerja fisik 16%, insentif 16%, beban kerja 37%, pengawasan 42%, dan kebijakan 42%. Tidak ada perbedaan yang signifikan antara kepuasan kerja di puskesmas rawat jalan dengan puskesmas rawat inap (p=0,317). Kepuasan kerja puskesmas rawat jalan ada pada faktor pengawasan, kebijakan Kepala Puskesmas, dan  motivasi. Pada puskesmas rawat inap berupa budaya kerja, jasa kapitasi, hasil pekerjaan, rekan kerja, keamanan dan keselamatan kerja, kesempatan meningkatkan keahlian dan keterampilan Kata Kunci: Kepuasan Kerja, Puskesmas, Rawat Inap, Rawat Jalan, Tenaga Kesehatan